Mathematical Modelling of Fluid Flow in Cone and Cavitation Formation - Milada KOZUBKOVÁ; Jana RAUTOVÁ (Transactions of the VŠB-Technical University of Ostrava, Mechanical Series, 2011)
Problem of cavitation is the undesirable phenomena occuring in the fluid flow in many hydraulic application (pumps, turbines, valves, etc.). Therefore this is in the focus of interest using experimental and mathematical methods. Based on cavitation modelling in Laval nozzle results and experience [1], [2], [4], following problem described as the water flow at the outlet from turbine blade wheel was solved. Primarily the problem is simplified into modelling of water flow in cone. Profiles of axial, radial and tangential velocity are defined on inlet zone. The value of pressure is defined on the outlet. Boundary conditions were defined by main investigator of the grant project – Energy Institute, Victor Kaplan’s Department of Fluid Engineering, Faculty of Mechanical Engineering, Brno University of Technology. The value of air volume was insignificant. Cavitation was solved by Singhal model of cavitation.